The influence of storage conditions and DNA extraction protocol on the results of molecular analysis of the European spruce bark beetle (Ips typographus L.) - Devetak, Zina (Acta silvae et ligni, 2023)
One of the key steps of the molecular identification of bark beetles is obtaining a sufficient quantity of high-quality DNA extract. In this study, we investigated the influence of different storage procedures for Ips typographus (L.) specimens and various DNA extraction protocols on the quantity and quality of DNA intended for use in molecular diagnostics. Adult beetles were frozen at -20 °C, either dry or in ethanol. We tested four different protocols for DNA extraction. We compared the quantity of extracted DNA and assessed its quality with PCR and Sanger sequencing. Different storage protocols had no significant effect on the quantity of DNA extracted. However, freezing specimens in ethanol provided higher-quality DNA for molecular applications. Only two of the extraction protocols produced sequenceable amplicons, and the difference in the amount of extracted DNA between them was not significant. We propose the optimal combination of storing specimens in ethanol at -20°C and using the Nucleospin Insect DNA extraction kit from Macherey Nagel, enabling a timeefficient identification process.
Keywords: early detection; ekstrakcijski postopek; molecular diagnostics; molekularna diagnostika; PCR; polimerazna verižna reakcija; polymerase chain reaction; Sanger sequencing; sekvenciranje po Sangerju; shranjevanje osebkov; specimen storage; total DNA extraction; zgodnje zaznavanje